Effect of insoluble surfactant on turbulent bubbly flows in vertical channels. (October 2017) - Lu, Jiacai; Muradoglu, Metin; Tryggvason, Gretar
Highlights: Direct numerical simulation (DNS) of bubbles with the insoluble surfactant by using a fronttracking / finite-volume method. Elastic numbers of the surfactant are varied to study their effects on the collective motion of nearly spherical bubbles in a turbulent upflow in a vertical channel. The reduction in flow rate by clean non-coalescing bubbles from wall layers is largely eliminated by the addition of surfactants. The addition of surfactants changes the void fraction distribution and flow structure of the bubbly upflow in the turbulent channel. Abstract: The effect of an insoluble surfactant on the structure of turbulent bubbly upflow in a vertical channel is examined by direct numerical simulations (DNS). For nearly spherical bubbles the presence of a surfactant reduces the lateral lift on the bubbles and changes the structure of the flow in major ways. Clean bubbles are driven to the walls by the lift force and the void fraction distribution has a well defined peak near the walls, resulting in significant reduction in flow rate. Bubbles with strong enough surfactants do not experience significant lateral lift and remain in the bulk flow. Indeed, when surfactant is present the addition of bubbles to a turbulent flow has relatively little effect on the flow, once the pressure gradient is adjusted to account for the reduced weight of the mixture.